Prognostic value of serum tumor abnormal protein in gastric cancer patients - LAN, FENG (Mol Clin Oncol, 2016)
Aberrant glycosylation of protein occurs in nearly all types of cancers and has been confirmed to be associated with tumor progression, metastasis and the survival rate of patients. The present study aimed to explore the prognostic value of tumor abnormal protein (TAP) in gastric cancer patients. TAP was detected in the blood of 42 gastric cancer patients and 56 healthy volunteers by using the TAP testing kit. Univariate and multivariate Cox regression analysis were performed to evaluate the prognostic value of TAP. In total, 64.3% of gastric cancer patients were positive for TAP, and TAP was significantly correlated with poor prognosis [progression-free survival (PFS), 4.2 vs. 12.6 months; P=0.043]. TAP [hazard ratio (HR), 64.487; P<0.01), differentiation (HR, 17.279; P<0.01) and TNM stage (HR, 45.480; P<0.01) were found to be independent predictive factors for PFS. Furthermore, Kaplan-Meier curves indicated that TAP is associated with a reduced PFS in gastric cancer patients. The results of the present study therefore indicated that the TAP test has significant prognostic value for gastric cancer patients.